PENGARUH PERENDAMAN BENIH MUCUNA (Mucuna bracteata) DALAM BEBERAPA KONSENTRASI H2SO4 TERHADAP PEMATAHAN DORMANSI - Siska Chiko Efendi; Hasri Gusman; Nalwida Rozen (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2019)
Mucuna bracteata is a Legume Cover Crop (LCC) which has many advantages compared to other LCC. The generative propagation of M. bracteata is very difficult because of the seed coat is hard and thick, so that it has a long dormancy period and low germination. Germination without seed treatment, the germination ability only 12% to 18.33%. The efforts are made to break the seed dormancy by soaking the seeds in the sulfuric acid (H2SO4) to remove the lignin layer in the seed coat. The present study objective was to determine the appropriate concentration of H2SO4 for breaking dormancy of M. bracteata seeds. This research was conducted at the Laboratory of the 3rd Campus Andalas University, Dharmasraya, in April to June 2019 using a Completely Randomized Design (CRD) consisted of 3 treatments with 4 replications. The seed treatments were some concentrations of H2SO4 namely 3%, 4%, and 5%. The observed variables were T50 break dormancy period, germination ability, abnormal germination, dead seed, first count test, index value, and maximum growth potential. The observation data were analyzed by an F test at a 5% level, followed by the Duncan’s New Multiple Range Test (DNMRT) at a level of 5%. The results showed that soaking of M. bracteata seeds in H2SO4 with a concentration of 3% was the best treatment, a T50 value of 8.75 days after planting with a germination capacity of 78.50%.